Molecular and quantitative animal genetics - Hasan Khatib (John Wiley & Sons, 2015)
"Animal genetics is a central topic in upper-level animal science programs. Filling a void in existing literature on animal science, Animal Genetics introduces genetic principles and presents their application in production and companion animals. The book details population and quantitative genetics, epigenetics, biotechnology, and breeding among other topics. Useful in upper-level studies, Animal Genetics is an irreplaceable educational resource" -- Provided by publisher